A Case Report on Riga Fede Disease - M. Khaja Khalid Nawaz; R. Nazriya (Highlights on Medicine and Medical Research Vol. 15, 2021)
Riga Fede disease is a traumatic ulceration on the ventral surface of the tongue that affects newborns and infants. It is a reactive traumatic mucosal disease characterized by persistent ulcerations of the oral mucosa. They’re frequently linked to natal, neonatal, and deciduous lower incisors that have erupted. The case of a one-month-old female newborn with a severe traumatic ulceration on the ventral surface of the tongue is presented in this article. To make the procedure less traumatic and allow for recovery, the newborn teeth were extracted.